Learning statistics for doctoral students with digital teaching materials - Ccanto, Florencio Flores; Maldonado, Daniel Marcos Chirinos; Condori, Juan Carlos Valenzuela; Aguirre, Gualverto Federico Quiroz; Lira, Marianella Marilú Villegas (International Journal of Innovative Research and Scientific Studies, 2024)
The purpose of this research is to determine whether or not there are significant improvements with respect to the use of didactic materials in the learning by competencies (conceptual, procedural and attitudinal) of statistical topics in postgraduate students. The study used a quantitative, correlational and descriptive approach with a quasi-experimental design and a deductive hypothetical methodology. The sample consisted of 58 postgraduate students of the Enrique Guzmán y Valle National University of Education who were segregated into two groups: control and experimental. The survey technique was applied and a questionnaire validated by experts was used as an instrument for data collection. Finally, the results obtained were subjected to the normality test to select the appropriate statistical method, thus determining that the most appropriate test for the study is the nonparametric Mann-Whitney U test which shows that there is a significant improvement with respect to the use of digital didactic material in the learning of postgraduate students with the method of competencies (conceptual, procedural and attitudinal). The conclusion is that learning with digital didactic materials in the area of statistics should be implemented to improve academic quality in all areas for postgraduate and undergraduate students in order to obtain better academic results. The implications are immediate for the postgraduate students since they improved their academic performance and they will be able to perform the multiplier effect in some educational center since many of them are university teachers of different universities.